Dietary influences on pancreatic amylase and small intestinal disaccharidase activities in cattle - Kreikemeier, K.K.; Harmon, D.L.; Gross, K.; Armendariz, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pancreatic alpha-amylase activity was 54% higher in cattle fed at twice maintenance energy than in cattle fed at maintenance and was 52% greater in hay-fed than grain-fed cattle. Increased pancreatic alpha-amylase activity probably represents increased secretion as well. Alpha-amylase activity in small intestinal digesta was greater with increased energy intake and with hay feeding. Small intestine mucosal disaccharidase activities in cattle were unaffected by diet. Lactase activity was highest in the proximal segment of the small intestine and low in both mid and distal segments. Maltase and isomaltase activities were low in the duodenum, but increased toward the jejunum and remained elevated through the terminal ileum.
Keywords: Beef; Pancreatic amylase; Intestine; Disaccharidase